Methods Of Developing Efl Learners’ Pronunciation, Fluency, And Speech Activity Through Music And Songs - Akbarova Dildora Rustamovna (International Journal of Pedagogics, 2025)
This article analyzes the advantages of using music and songs in the process of developing EFL learners’ pronunciation, fluency, and speech activity, as well as the effects of music and its elements on learners’ consciousness. The author of the article has attempted to rely on the research of many scholars and her own scientific investigations while covering these issues.